Unsur Intrinsik Folklor Lutung Kasarung Cerita Rakyat Jawa Barat - Dea Warda; Dinda Syamsiah (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
Lutung Kasarung is a folk tale from West Java that can be famous among the public. This story tells about a handsome prince named Sanghyang Guruminda who was punished by being thrown to earth for making a mistake in the form of a lutung. Sanghyang Guruminda got lost in a forest so he was named Lutung Kasarung. In Sundanese Lutung Kasarung means lost Lutung. The popularity of Lutung Kasarung makes the other two characters, namely Purbasari and Purbararang, look like side characters, in fact, these siblings characters play an important role in the development of the storyline. This research aims to analyze the intrinsic elements contained in the Lutung Kasarung folklore. The formulation of this story problem includes: How is the journey of lutung kasarung to return to its original form? How is the plot of the lutung kasarung folk story? What mandate can be taken from the folk tale of lutung kasarung?. The research methods used are qualitative methods and Library Studies. Data sources are collected through literature studies that use various literature sources, including articles, journals, and websites that discuss Lutung Kasarung folklore. The analysis used is literary theory according to Meyer Howard Abrams, which is objective theory. An objective approach looks at the work of an autonomous object. It means, literary works can stand alone without involving things that are outside the work such as politics, economy, and others. Therefore, the focus of the objective approach is the work itself. The research results in this story show loyalty and sacrifice in the character of Lutung Kasarung, the characters in this story describe honor and strong inner strength with the outside world. The recommendation from this research is the need for further study development because it is still less related to the symbolism in this folklore, as well as efforts to preserve in folklore as part of cultural identity that can educate the younger generation to still preserve the noble values of our ancestors.